2018
DOI: 10.3389/fvets.2018.00175
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Antibodies in Veterinary Medicine: An Update

Abstract: The production of recombinant antibodies has had a tremendous impact on several research fields, most prominently in biotechnology, immunology and medicine, enabling enormous advances in each. Thus far, a broad diversity of recombinant antibody (rAb) forms have been designed and expressed using different expression systems. Even though the majority of rAbs approved for clinical use are targeted to humans, advances in veterinary medicine seem promising. The aim of this mini-review is to present an update regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Along with the increasing need in the market, developments of therapeutic antibodies are being made to tackle severe infectious human diseases such as dengue fever [ 25 ], influenza [ 26 ], Ebola [ 27 ], and COVID-19 [ 28 ]. Efforts to develop therapeutic antibodies against animal diseases are also actively being made in veterinary medicine [ 29 , 30 ]. However, success has been limited in controlling swine diseases, which is one of the most valuable agricultural industries worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the increasing need in the market, developments of therapeutic antibodies are being made to tackle severe infectious human diseases such as dengue fever [ 25 ], influenza [ 26 ], Ebola [ 27 ], and COVID-19 [ 28 ]. Efforts to develop therapeutic antibodies against animal diseases are also actively being made in veterinary medicine [ 29 , 30 ]. However, success has been limited in controlling swine diseases, which is one of the most valuable agricultural industries worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that antigen targeting to different DC receptors results in increased antibody production, cell activation, and cytokine secretion [20]; thus, antigen targeting using recombinant antibodies has been presented as a potential tool for effective vaccination in veterinary medicine [21]. The persistence of PRRSV in porcine farms over time continues to drive the constant development of vaccines to prevent infection outbreaks and maintain farms in a negative status to reduce the economic impact of PRRSV [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The progress on recombinant monoclonal antibody production is beneficial for multiple fields of veterinary medicine [1]. At the moment therapeutic monoclonal antibodies (mAbs) are mainly produced for dogs [1].…”
Section: Introductionmentioning
confidence: 99%
“…The progress on recombinant monoclonal antibody production is beneficial for multiple fields of veterinary medicine [1]. At the moment therapeutic monoclonal antibodies (mAbs) are mainly produced for dogs [1]. Lokivetmab (Cytopoint ® ; Zoetis Belgium SA, Louvaisn-la-Neuve, Belgium) is a caninised, anti-interleukin-31 (IL-31) monoclonal antibody, approved for the treatment of canine atopic dermatitis (cAD) [2].…”
Section: Introductionmentioning
confidence: 99%